An Analysis of the Legal Standard in the Fight Against Torture and Treatment of Prisoners under International Law: What Prospect for Application under Cameroonian Law? - N. V. Minang; N. C. Nguindip (Law and Safety)
This article seeks in highlighting the fact that prohibiting torture, cruel, inhumane and degrading treatment of persons is an important aspect of human right specificities articulated in relevant human right dispositions especially the main Universal Declaration of Human Right 1948, and has given responsibilities to States in ensuring the effective protection of this right by preventing their violations. The article also indicates that, though this right has occupied an international recognition to States who are parties to the available relevant dispositions, violating its provision will constitute grave injury and arbitrary treatment on the dignity and integrity of the human race. Cameroon in its compliance with the international standard set, has contributed enormously by enacting credible laws which varies from its constitution, criminal codes, and other relevant provision all in the aim of safeguarding and ensuring that this right should be treated with lots of human protection and security. Even though with efforts laid in place by the country through its various legal and institutional dispositions, prohibition and protection has continued to be considered as a nightmare, as we continue in experiencing violations of this fundamental right by those who were vested with the powers and competent in ensuring and securing this sacred right. The violations experienced have really provoked lots of questioning as to the place occupied, and the outcome of the Cameroon Human Right system in combating and punishing those who interrupts the assurance of this fundamental human right?